Variation in job titles within the nursing workforce. Issue 23 (7th September 2017) - Leary, Alison; Maclaine, Katrina; Trevatt, Paul; Radford, Mark; Punshon, Geoffrey
Abstract : Aims and objectives/background: The work of specialist nursing has been under scrutiny for many years in the UK due to a perception that it is not cost‐effective. A common issue is the lack of consistency of job titles, which causes confusion to the public, employing organisations, colleagues and commissioners of services. Lack of consistency has implications for the wider perception of advanced specialist practice in the worldwide community and the workforce more generally. This study aims to understand the variation in job titles in the UK population. Methods: A pre‐existing data set of accrued studies into the work of nurses working in specialisms was mined for insight ( N  = 17, 960). This study used knowledge discovery through data and descriptive statistics to perform secondary analysis. Results: Mining these data revealed 595 job titles in use in 17, 960 specialist posts once the specialism had been removed. The most commonly used titles were Clinical Nurse Specialist, Nurse Specialist/Specialist Nurse, Advanced Nurse Practitioner and Nurse Practitioner. There were three other primary groupings. These were variants with a specialist or technical prefix of suffix, for example Nurse Endoscopist, variants of seniority such as trainee, senior nurse for [specialism] or variants of function such as Nurse Prescriber. The clustering was driven primarily by pay band. A total of 323 posts were recorded as holding titles such as Advanced Nurse Practitioner or Specialist Nurse who were not registered with the Nursing & Midwifery Council. Relevance to clinical practice: In this data set, there is a large array of titles, which appear to have little relationship with other factors like education. This is confusing to the public, employers and those commissioning services. It also demonstrates that the previous assumptions by Council for Healthcare Regulatory Excellence that advanced practice labels are associated with career progression are unsound and should be addressed by the regulator.